Docosahexaenoic acid reduces microglia phagocytic activity via miR-124 and induces neuroprotection in rodent models of spinal cord contusion injury. (11th April 2019) - Yip, Ping K; Bowes, Amy L; Hall, Jodie C E; Burguillos, Miguel A; Ip, T H Richard; Baskerville, Tracey; Liu, Zhuo-Hao; Mohamed, Moumin A E K; Getachew, Fanuelle; Lindsay, Anna D; Najeeb, Saif-Ur-Rehman; Popovich, Phillip G; et al.
Abstract: Microglia are activated after spinal cord injury (SCI), but their phagocytic mechanisms and link to neuroprotection remain incompletely characterized. Docosahexaenoic acid (DHA) has been shown to have significant neuroprotective effects after hemisection and compression SCI and can directly affect microglia in these injury models. In rodent contusion SCI, we demonstrate that DHA (500 nmol/kg) administered acutely post-injury confers neuroprotection and enhances locomotor recovery, and also exerts a complex modulation of the microglial response to injury. In rodents, at 7 days after SCI, the level of phagocytosed myelin within Iba1-positive or P2Y12-positive cells was significantly lower after DHA treatment, and this occurred in parallel with an increase in intracellular miR-124 expression. Furthermore, intraspinal administration of a miR-124 inhibitor significantly reduced the DHA-induced decrease in myelin phagocytosis in mice at 7 days post-SCI. In rat spinal primary microglia cultures, DHA reduced the phagocytic response to myelin, which was associated with an increase in miR-124, but not miR-155. A similar response was observed in a microglia cell line (BV2) treated with DHA, and the effect was blocked by a miR-124 inhibitor. Furthermore, the phagocytic response of BV2 cells to stressed neurones was also reduced in the presence of DHA. In peripheral monocyte-derived macrophages, the expression of the M1, but not the M0 or M2 phenotype, was reduced by DHA, but the phagocytic activation was not altered. These findings show that DHA induces neuroprotection in contusion injury. Furthermore, the improved outcome is via a miR-124-dependent reduction in the phagocytic response of microglia.